Analisis Efisiensi dan Efektivitas Anggaran Pendapatan Belanja Daerah Terhadap Realisasi Anggaran Pembangunan di Sektor Pendidikan Kabupaten Jombang - Ilyas Nurul Azam (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2020)
Performance indicators for development activities are quantitative and qualitative measures that describe the level of achievement of a predetermined activity which is categorized into inputs, outputs, outcomes, benefits and impacts of regional development activities. This study specifically analyzes how: (1) the consistency between the Regional Expenditure Budget and the realization of the development budget in the Jombang Regency government's education sector from a financial perspective, (2) the level of efficiency and effectiveness of the development budget in the education sector which is allocated from the Budget Revenue Expenditures The area as seen from the realization of the budget, expenditure plans and realization of expenditure in the Jombang Regency government's education sector. Measurement analysis using the Balance Score Card method of financial aspects and Value For Money levels of efficiency and effectiveness. The results of this study indicate that: (1) there is consistency between the Regional Expenditure Budget and the realization of the development budget in the Jombang Regency government's education sector from a financial perspective, (2) the development budget in the education sector is allocated from the Regional Expenditure Budget from a financial perspective. budget realization, expenditure plans and realization of expenditure in the education sector of the Jombang Regency government are said to be efficient with a value of more than 90% and an effectiveness level of 100% taking into account the outcomes achieved